Economic geography and Urban environmental pollution - Martin Quaas; Andreas Lange (University of Heidelberg, Department of Economics, 2004)
This paper studies Krugman's (1991) core-periphery model and extends it to include environmental pollution. We present the first analytic proof that only an even spreading of the firms over both of the two regions or a complete agglomeration of all manufacturing firms in one region are possible in Krugman's (1991) model. It is shown that, in a model including local environmental pollution, a third and more realistic type of equilibrium may occur in which most of the manufacturing firm locate in one region, but some manufacturing remains in the other.
Keywords: R12; J61; Q20; 330; Geographical Economics; Environmental Economics; Pollution; Labor Mobility; Zentrum-Peripherie-Beziehungen; Umweltbelastung; Umweltökonomik; Standortwahl; Arbeitsmobilität; Theorie